The Relationship between Knowledge, Attitudes and Husband Support with Patterns of Breastfeeding in the Working Area of the Wonorejo Health Center, Samarinda City in 2022 - Winda Ayu Ginanti; Satriani; Jamil Anshory (Formosa Journal of Science and Technology, 2022)
Low breastfeeding coverage in Indonesia is influenced by many factors, and Green's theory determines these factors by three factors: trend, support and encouragement. Predisposing factors, eg. (mother's age, education, knowledge, attitude, profession, socio-culture), support (health services and media) and support from health services influence mother's breastfeeding behavior, encouragement (family and community support). Many additional factors, including education, the mother's occupation, knowledge, attitudes, the role of government officials, media attention, the role of the parents, and the support of the spouse or partner, may also have an impact on exclusive breastfeeding.